PERTANGGUNGJAWABAN PIDANA KE YANG MENERIMA PENTRANSFERAN UANG DARI PIHAK LAIN SEBAGAI HASIL PERJUDIAN DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAAN TINDAK PIDANA PENCUCIAN UANG - TITA PRASPA DAYANTI; Go Lisanawati; Daniel Djoko Tarliman (Perpustakaan Universitas Surabaya, 2018)
The purpose of this scientific journal writing is as a requirement for graduation and obtaining a Bachelor of Law degree at the Faculty of Law, University of Surabaya. Practical objectives of the writing of this thesis to be able to know whether the initial (criminal) KE can be subject to criminal liability when viewed from Acts Number 8 Year of 2010 on Prevention and Eradication of Money Laundering Crime. The criminal action committed by the KE about gambling may be subject to criminal responsibility under Article 3 of Acts Number 8 Year of 2010 regarding the Prevention and Eradication of Money Laundering Crime. The acts committed by the KE have fulfilled the entire elements of criminal liability. The action of the KE has fulfilled the whole elements as Article 3 of Acts Number 8 Year 2010 on Prevention and Eradication of Money Laundering Crime, which is intentionally committed in which KE as a bookie, the acts committed by KE can be subject to criminal sanction as Article 3 of Acts Number 8 Year of 2010 concerning the Prevention and Eradication of Money Laundering with a maximum imprisonment of 20 (twenty) years or a fine of not more than Rp 10,000,000,000 (ten billion rupiahs).